Incarnation The Person and Life of Christ - Torrance, Thomas F. (IVP Academic IVP Academic, 2008)
The late Thomas F. Torrance has been called "the greatest Reformed theologian since Karl Barth" and "the greatest British theologian of the twentieth century" by prominent voices in the academy. His work has profoundly shaped contemporary theology in th
Keywords: Jesus Christ -- Person and offices. Incarnation. Jesus Christ